Evaluation of The Physical Training Program of Table Tennis Clubs in Bengkulu City - Al Ilham; Muhammad Faisal Lutfi Amri; Juni Isnanto; Sulasikin Sahdi Kadir (Asian Journal of Social and Humanities, 2022)
The problem in  this study is that  athletes always experience fatigue when competing in national events  , which is due to their poor physical condition.   The goal in this study was to evaluate the physical exercise program of coaching table tennis clubs. This research was conducted at a table tennis club in the city of Bengkulu.  This type of research is aqualitative research with the CIPP  method through a  qualitative approach. CIPP consists of four stages, namely: Context, Input, Process, Product. Data were obtained through observations, questionnaires, interviews and documentation studies.  This study uses a non-statistical qualitative analysis method, where the data reduction component, and data presentation are carried out in conjunction with the data collection process after being collected, the three components are analyzed (data reduction, data presentation, conclusion drawing) interact. The results of this study show that (1) The process of eligibility and qualification mechanisms for coaches and athletes of table tennis clubs in Bengkulu City includes PTM. Fortifications, PTM. Post, PTM. Tebeng is already relatively decent. (2) The implementation of the physical training program has not been running well, in the coach and athlete sectors. (3) The facilities and infrastructure owned by table tennis clubs in Bengkulu City are still categorized as not good because they are only PTM. Posts that have adjusted facilities and infrastructure according to PTMSI standards while PTM. Fortifications and NCDs. Tebeng still needs to benahi.